Promotion of the Intangible Cultural Heritage of Kampung Budaya Jalawastu in Commercial Photography - sans, Rahmadi madi; Sudradjat, Oky Mauludya; Prasetya, Rifky Yoga (Universitas Pasundan, 2025)
This research explores seven cultural elements in Jalawasu Cultural Village using qualitative methods. The focus includes language, knowledge, social, technological, livelihood, religious, and artistic systems. Through participatory observation, in-depth interviews, and visual documentation, data was obtained from community leaders and local residents. A commercial photography approach was used to capture the visual essence of each cultural element whose culture will be promoted through the Instagram platform and website. The aim is to increase awareness and appreciation of the rich culture of Jalawastu Cultural Village among the wider community. This research concludes that the preservation and promotion of seven cultural elements in Jalawastu Cultural Village is important to maintain local cultural identity in the midst of modernization. Recommendations are given for the development of a more effective cultural promotion strategy through Instagram and website media.